Investigation on the Compatibility of Extracted Plant Pigments in Emulsion Paints and the Effects of Inhalation on the Liver Enzymes of Wistar Rats - Mfon, Bobson, Promise-Godsfavour; Nonyelum, Ezekwesili, Chinwe; Ikechukwu, Ubaoji, Kingsley (American Journal of Bioscience and Clinical Integrity, 2025)
The compatibility of Curcuma longa rhizome and Hibuscus sabdariffa flowers pigment extracts in white emulsion paint and the effect of inhalation on the liver enzymes of Wistar rats were investigated. Wistar rats weighing between 120g to 150g were randomized into eight groups (A – H) of five rats each. Different group of rats (groups A to H) were exposed to different mixtures of organic and inorganic colourants in emulsion paint for six months. Group A was exposed to white emulsion paint only, Group B was exposed to 20mls of Curcuma longa paste in white emulsion paint. Group C was exposed to 20mls of Hibiscus sabdariffa pigment in white emulsion paint. Group D was exposed to 20mls (1:1) combination of C. longa and H. sabdariffa. Group E was exposed to 20mls of C. longa paste and inorganic yellow oxide paste in white emulsion paint, Group F was exposed to 20mls (1:1) combination of H. sabdariffa paste and inorganic red oxide paste in white emulsion paint. Group G was exposed to 20mls (1:1) combination of yellow oxide paste and red oxide paste in white emulsion paint. Group H was the Normal Control which was not exposed to paint. All animals were allowed free access to commercial rat mash and distilled water throughout the six months of exposure. The Curcuma longa paste and Hibiscus sabdariffa paste were completely miscible and compatible with other components of the paint although they degraded or faded in colour faster on exterior application than interior application. The fading of the colours exposed externally compared to the ones exposed internally can be attributed to the effect of sunlight, rain and intense temperature from the ultra-violet rays. The Wistar rats in each group were exposed to the different paint sample through inhalation. The result revealed that there was a significant increase (p<0.05) in the serum ALT activity of the Wistar rats in Group E exposed to 2mls C. longa and inorganic yellow oxide paste in white emulsion paint from 1st to 6th month of exposure. However, Group G also showed increase serum ALT at 4th and 6th month of exposure compared to the normal control group H. Significant increase was also recorded in the serum AST activity of Group B, C, D, E, F and G from 2nd to the 6th month of exposure compared to the normal control group H. Also, the serum ALP activity of Group A, B, C, D, E, F and G recorded significant increase from the 1st to the 6th month of exposure compared to the normal control group H. Therefore, inhalation of the paint fume by the Wistar rats elicited significant alterations in the concentration of ALT, AST and ALP. This indicated that paint chemicals can adversely affect the liver enzyme due to prolonged inhalation of the paint fume by the Wistar rats.